2008
DOI: 10.17221/345-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the stage of maturity on the leaf percentage of lucerne and the effect of additives on silage characteristics

Abstract: ABSTRACT:The first part of the study concerns the effect of the stage of maturity on nutrient content and leaf percentage of lucerne (Medicago sativa). The plants of lucerne were harvested and analysed at several stages of growth. The crop yield and changes in the concentration of nutrients were determined. The leaf percentage from whole herbage and leaf yield were determined as well. The leaf percentage at the growth stage of small buds was significantly (P < 0.05) higher than at the growth stage of bloom in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Thus, for this purpose were created varieties with a higher percentage of leaves (varieties with shorter internodes, with a greater number of leaves floors, or pentafoliate leaves varieties). Rotili et al (2001), Lamb et al (2006), Petkova and Panayotova (2007), Tyrolová and Výborná (2008), highlighted these issues in their studies. The leaves/stems ratio varies according to numerous factors: the variety grown, fertilizer application, number of cuts, climatic conditions etc., but the obtained results showed that the phenological phase when alfalfa is harvested also has a predominant influence on this indicator.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for this purpose were created varieties with a higher percentage of leaves (varieties with shorter internodes, with a greater number of leaves floors, or pentafoliate leaves varieties). Rotili et al (2001), Lamb et al (2006), Petkova and Panayotova (2007), Tyrolová and Výborná (2008), highlighted these issues in their studies. The leaves/stems ratio varies according to numerous factors: the variety grown, fertilizer application, number of cuts, climatic conditions etc., but the obtained results showed that the phenological phase when alfalfa is harvested also has a predominant influence on this indicator.…”
Section: Resultsmentioning
confidence: 99%
“…Although alfalfa crop fields have the appearance of a uniform mass consisting of stems, leaves, flowers and petioles, each of these parts differ in terms of chemical composition (Tyrolová and Výborná, 2008;Vasileva, 2013;Vyas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a lack of WSC in crops wilted for long periods [74]. Low concentrations of WSC in herbage, even in inoculated ones, can lead to a decrease in silage quality [75,76].…”
Section: Water Soluble Carbohydrates (Wsc)mentioning
confidence: 99%
“…Feed quality, and therefore ruminal degradability, is influenced by several factors, with the most important stage of maturity of forage, forage species, environmental effects (location in combination with temperatures and precipitation), agronomic management, site of growth, and processing such as treatment and preservation (Pozdíšek and Vaculová, 2008;Tyrolová and Výborná, 2008;Jančík et al, 2009). Different patterns of maturation in forage species have a profound effect on animal performance in ruminants (Hetta et al, 2004).…”
mentioning
confidence: 99%